Fragile states and protection under the 1969 African Refugee Convention - Wood, T (Refugee Studies Centre, University of Oxford, 2013)
Current practice in African states highlights both the potential and the limitations of the 1969 African Refugee Convention in providing protection to persons displaced from fragile states.